Combining Tumor Microenvironment Modulating Nanoparticles with Doxorubicin to Enhance Chemotherapeutic Efficacy and Boost Antitumor Immunity. (14th September 2018) - Amini, Mohammad Ali; Abbasi, Azhar Z; Cai, Ping; Lip, HoYin; Gordijo, Claudia R; Li, Jason; Chen, Branson; Zhang, Li; Rauth, Andrew M; Wu, Xiao Yu
Abstract: Background: Tumor microenvironment (TME) and associated multiple factors are found to contribute to the failures in cancer therapies, including chemo- and immunotherapy. Here we report a new multimodal strategy that uses a bioreactive multifunctional hybrid polymer-lipid encapsulated manganese dioxide nanoparticle (PLMD NP) system to remodel the TME, suppress drug resistance factors, reverse immunosuppressive conditions, and enhance chemotherapy efficacy. Methods: The influence of PLMD NPs on enhancing cellular uptake in EMT6 mouse breast cancer cells and tumor penetration of doxorubicin (DOX) in EMT6 orthotopic breast tumor mouse model was evaluated using confocal microscopy (n = 3–4). Immunohistochemistry was employed to examine the effect of PLMD NPs on downregulating hypoxia-induced drug resistance proteins and anticancer activity of DOX (n = 3–4). The efficacy of the combination therapy with PLMD NPS and DOX was assessed in murine EMT6 (n = 15–23) and 4T1 (n = 7) orthotopic breast tumor mouse models. Rechallenge and splenocyte transfer were performed to validate the stimulation of adaptive tumor immunity in the surviving mice. Results: PLMD NPs enhanced intratumoral penetration and efficacy of DOX, and reduced intratumoral expression of P-glycoprotein, p53, and carbonic anhydrase IX by 74.5%, 38.0%, and 58.8% vs saline control, respectively. Combination treatment with PLMD NPs and DOX increased the number of tumor-infiltrated CD8 + T cells and resulted in up to 60.0% complete tumor regression. Of naïve mice (n = 7) that received splenocytes from the PLMD+DOX–treated surviving mice, 57.1% completely suppressed tumor growth whereas 100% of mice that received splenocytes from DOX-treated mice (n = 3) and the control group (n = 7) showed rapid tumor growth. Conclusions: The clinically suitable PLMD NPs can effectively downregulate TME-associated drug resistance and immunosuppression. The combination therapy with PLMD NPs and DOX is a multimodal and translational treatment approach for enhancing chemotherapeutic efficacy and boosting antitumor immunity.